The adaptor protein p40(phox) as a positive regulator of the superoxide-producing phagocyte oxidase - Kuribayashi, Futoshi (Oxford University Press, 2002)
Activation of the superoxide-producing phagocyte NADPH oxidase, crucial in host defense, requires the cytosolic proteins p67(phox) and p47(phox). They translocate to the membrane upon cell stimulation and activate flavocytochrome b(558), the membrane-integrated catalytic core of this enzyme system. The activators p67(phox) and p47(phox) form a ternary complex together with p40(phox), an adaptor protein with unknown function, comprising the PX/PB2, SH3 and PC motif- containing domains: p40(phox) associates with p67(phox) via binding of the p40(phox) PC motif to the p67(phox) PB1 domain, while p47(phox) directly interacts with p67(phox) but not with p40(phox). Here we show that p40(phox) enhances membrane translocation of p67(phox) and p47(phox) in stimulated cells, which leads to facilitated production of superoxide. The enhancement cannot be elicited by a mutant p40(phox) carrying the D289A substitution in PC or a p67(phox) with the K355A substitution in PB1, each being defective in binding to its respective partner. Thus p40(phox) participates in activation of the phagocyte oxidase by regulating membrane recruitment of p67(phox) and p47(phox) via the PB1–PC interaction with p67(phox).